Ideas and Practices of Democracy: the reactualisation of isonomy and isegory within social movements - Masse, Cédric (Revista de Sociologia e Política, 2017)
How is public participation achieved within social movements? Does it fundamentally rely on politico-economic conditions or does it primarily refer to the ideal or discursive sphere? This problem is addressed through a critical synthesis of theories that deal with this issue (resource mobilisation theories, political process model, Jürgen Habermas, Richard Sennett and Alexis de Tocqueville) and, empirically, through the observation and analysis of concrete modalities of public participation within Portuguese social movements (from a “qualitative” sociology or an ethnography of some movements carried out in Lisbon between 2010 and 2012). In this context, as elsewhere, public participation especially rests upon two linked ethical and political axioms: isonomy - the same law for everyone, the economic basis of public participation - and isegory - the same time to speak for everyone, the ideal foundation of public participation. Thus, to understand the how of public participation within social movements, it is necessary to overcome the traditional dichotomy between materialistic theories that stress the economic dimension of public participation and social movements, and idealistic approaches that address the symbolic and cultural aspects.